From Darkness to Self-Reliance: A Community-Driven Model for Sustainable Public Lighting in Soropia Village - Simanjuntak, Raja Agung Hasudungan; Badia, Bahdin Ahad; Aji, Angga Asteriasti; Darwis, Mardis; Putra, Fachrizal Cesar; Putra, Muhammad Idris; Rahman, La (Teras Kampus as a member of PT Palem Edukasi Nusantara, 2025)
This initiative addressed the critical deficit in public street lighting in Soropia Village, which hindered safety, mobility, and economic activity after dusk. Moving beyond mere infrastructure provision, the project's core objective was to establish a sustainable, community-owned model for public lighting through comprehensive technical capacity building and institutional development. Employing a participatory rural appraisal (PRA) framework, the project engaged 35 local participants in a multi-phase process over June 2025. This included collaborative identification of problem areas, co-design of technical solutions using locally-sourced and recycled materials, and an intensive, hands-on workshop. The technical design specifically utilized recycled metal pipes fabricated by participants, reinforced concrete foundations (40cm x 40cm x 60cm), and a safe electrical system with LED technology, proper grounding, and overcurrent protection connected to the existing grid. The project yielded three primary outcomes: 1) The successful installation of multiple functional, community-fabricated street lights at strategic locations; 2) A measurable enhancement of technical skills among participants, enabling independent maintenance and replication; and 3) The emergence of a formalized community task force committed to the project's longevity. Pre- and post-workshop assessments showed a 75% increase in technical self-efficacy scores among participants. The Soropia model demonstrates that integrating technical education with community-led implementation and early institutionalization fosters profound and sustainable empowerment. The transformation of participants from passive beneficiaries to active managers of their infrastructure is the key success metric. For scalability, we recommend integrating a micro-enterprise component to ensure financial sustainability for ongoing maintenance and expansion, thereby creating a replicable blueprint for rural infrastructural development.